2017
DOI: 10.1039/c7sm00290d
|View full text |Cite
|
Sign up to set email alerts
|

Drop transport and positioning on lubricant-impregnated surfaces

Abstract: We demonstrate the transport and positioning of water droplets on macro-patterned lubricant-impregnated surfaces. The macro-patterning produces menisci features in the impregnating liquid layer which interact with a droplet via a capillary mechanism similar to the Cheerios effect. These interactions control the droplet motion and positioning on an otherwise completely slippery surface. We present experimental results using a V-shape channel geometry as a model system. The interaction between deformations on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…[81] A similar patterned V-shaped surface also allowed for the positioning and movement of droplets based on capillary interactions. [82] Recently, we investigated the capability of different liquids to displace the lubricant from higher surface energy regions and showed that both high and low surface tension liquids can replace it, thereby forming droplets sharply following underlying surface (1) is coated with photoresist (2), irradiated through a photomask, and developed to create the surface pattern (3). Vapor-phase fluoro silanization used to create fluorinated surface functionalities at the exposed surface regions (4); the protected surface regions remain nonfunctionalized after removal of the photoresist (5).…”
Section: Patterned Slipsmentioning
confidence: 99%
“…[81] A similar patterned V-shaped surface also allowed for the positioning and movement of droplets based on capillary interactions. [82] Recently, we investigated the capability of different liquids to displace the lubricant from higher surface energy regions and showed that both high and low surface tension liquids can replace it, thereby forming droplets sharply following underlying surface (1) is coated with photoresist (2), irradiated through a photomask, and developed to create the surface pattern (3). Vapor-phase fluoro silanization used to create fluorinated surface functionalities at the exposed surface regions (4); the protected surface regions remain nonfunctionalized after removal of the photoresist (5).…”
Section: Patterned Slipsmentioning
confidence: 99%
“…Lubricated topographies, however, would be able to overcome such shortcomings thanks to the pinning introduced by the feature and the droplet's tendency to adhere to the lubricating liquid (whilst being completely mobile). Furthermore, directed motion on lubricated topographies could be created with a vanishingly small tilt of the surface [5,6,[11][12][13][14]22].…”
Section: Discussionmentioning
confidence: 99%
“…The surfaces were rendered superhydrophobic with a nanoparticle based coating (Glaco Mirror Coat Soft 99 Co.). They were subsequently immersed in a bath of silicone oil (Sigma-Aldrich, 20cSt) and withdrawn vertically at a controlled rate of 1 mms −1 to create a uniform lubricant layer of thickness, t ≈ 13 µm [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations